Dynamics of a light-driven molecular rotary motor in an optical cavity - In Seong Lee; Michael Filatov; Seung Kyu Min (Nature Communications)
Abstract Light-driven rotary molecular motors transform the energy of light to mechanical motion (rotation) of one part of the molecule with respect to another. For a long while, various stimuli orthogonal to the motor’s source of energy were used to manipulate its operational characteristics; such as the speed of rotation. However, these stimuli employed predominantly chemical means and were difficult to apply in situ during the motor’s operation. Here, we show that the characteristics of the excited state decay in molecular motor molecules can be altered due to strong light-matter interactions occurring in optical cavities. By performing nonadiabatic simulations of the motor’s photodynamics in the presence of strong coupling with a cavity mode, we find that the coupling with a mode detuned off resonance with the molecular optical transition offers a means to considerably increase the excited state decay lifetime and to either inhibit or slow down the motor’s rotation.